System-wide targeted analysis of oxylipins and lipoproteins in chronic peripheral neuropathic pain—an explorative study - Mika Jönsson; Emmanuel Bäckryd; Stefan Ljunggren; Nina Ottosson; Amaia Jauregi-Miguel; Sara I. Liin; Antonio Checa; Craig E. Wheelock; Bijar Ghafouri (PAIN Reports)
Abstract. Introduction:. Neuroinflammation and oxidative dysfunction, and their reciprocal interplay, are critically involved in the pathophysiology of chronic neuropathic pain (NeuP). Numerous studies have investigated the crosstalk between inflammatory biomolecules such as cytokines, chemokines, and neuronal cells. However, the impact of immunomodulatory lipoproteins and oxylipins in NeuP pathophysiology is far less explored. Methods:. Using a combination of techniques, we uncovered altered lipoprotein composition in high-density lipoproteins (HDLs) and low-density lipoproteins (LDLs) with complementary alterations in the plasma profile of oxylipins and cytokines among patients. Results:. Lower level of apolipoproteins in patient HDL and 2 isoforms of acute phase serum amyloid A (SAA) with higher levels in patients was found. The constitutively expressed SAA4 was detected in 6 isoforms in patients, but only 2 isoforms were detected in healthy controls. In LDL, lysozyme C and 2 isoforms of SAA were exclusive to patients. Analysis of protein carbonylation showed oxidation of 6 proteins in HDL, of which 3 were unique to patients. No oxidized proteins were observed in LDL. Oxylipin analysis revealed 13 octadecanoids that were significantly downregulated in patients, of which 7 demonstrated significant activating effects on the Kv7.2/7.3 channel, which is anticipated to dampen neuronal signalling in sensory afferents. Among the significant octadecanoids, 9-HODE showed most prominent facilitating effects on Kv7.2/7.3 channel activation. Conclusion:. These results present a previously unexplored network of integrated alterations of lipoproteins, octadecanoids, and cytokines in patients suffering from NeuP, indicative of deviant immuno-protective functioning across several biological systems including lipid metabolic processes, inflammation, and Kv7.2/7.3 signalling.